Shop class as soulcraft : an inquiry into the value of work - Crawford, Matthew B. (2010)
A philosopher and mechanic extolls the virtues of manual labor, describing how the satisfactions and challenges of creating with one's own hands promotes a sense of connection to life that office work suppresses.
A brief case for the useful arts -- The separation of thinking from doing -- To be master of one's own stuff -- The education of a gearhead -- The further education of a gearhead : from amateur to professional -- The contradictions of the cubicle -- Thinking as doing -- Work, leisure, and full engagement.
London edition has title: The case for working with your hands.
Includes bibliographical references (pages 215-238) and index.
Keywords: Manual work; Work; Job satisfaction; Manual work; Work; Job satisfaction